2022
DOI: 10.1371/journal.pone.0269743
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on perceived publication pressure among academic researchers in Canada

Abstract: The phenomenon of “publish-or-perish” in academia, spurred on by limited funding and academic positions, has led to increased competition and pressure on academics to publish. Publication pressure has been linked with multiple negative outcomes, including increased academic misconduct and researcher burnout. COVID-19 has disrupted research worldwide, leading to lost research time and increased anxiety amongst researchers. The objective of this study was to examine how COVID-19 has impacted perceived publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 62 publications
(69 reference statements)
0
14
0
Order By: Relevance
“…This suggests that researchers in the field of radiology are increasingly promoting their research findings. Increasing use of promotional language is thought to be a reaction of researchers to increasing publication pressure and publication bias favoring positive results over negative results [2][3][4][5][6]. Note that previous research has shown that radiology researchers also perceive publication bias as a widespread phenomenon [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that researchers in the field of radiology are increasingly promoting their research findings. Increasing use of promotional language is thought to be a reaction of researchers to increasing publication pressure and publication bias favoring positive results over negative results [2][3][4][5][6]. Note that previous research has shown that radiology researchers also perceive publication bias as a widespread phenomenon [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, journals, and particularly those with a high impact factor (IF), only accept a minority of submitted manuscripts. Not surprisingly, publication pressure on academic researchers is generally regarded as high [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could argue that regardless of having children or any care responsibilities, intense pressure would affect academics and the quality of their work adversely. Indeed, the pressure to publish more (and faster) is found to have the potential to decrease scientific quality (Merck KGaA, Darmstadt, Germany & Oxford Economics, 2021), has been linked to burnout and this pressure was intensified during the pandemic (Suart et al., 2022). In this study, alongside a certain level of increase in perceived pressure regarding research productivity, 35.4% of the respondents reported a level of burnout scored 80 and above (out of 100, which is the highest score for agreeing with the statement ‘I experienced burnout during the pandemic’).…”
Section: Discussionmentioning
confidence: 99%
“…While studies have already shown that women have higher levels of stress and anxiety (Hankin, et al, 2007;Savitsky, et al, 2020;Suart, Neuman & Truant, 2022) and react differently to them than men (Bekker & van Mens-Verhulst, 2007), our study points out that the emotional effects of first confinement of covid-29 were different in men and women and this was aggravated when they were in the subgroup of younger career researchers, consistently with some recent studies (Suart, Neuman & Truant, 2022). Uncertainty related to the sudden and unexpected transition to distance learning and concern about the future, including academic career assessment procedures (Sahu, 2020), could have played a significant role, with adverse effects on the psychological health of this subgroup of younger individuals.…”
Section: Discussionmentioning
confidence: 99%